Influencia de la psicomotricidad fina en la vida diaria de las personas con discapacidad intelectual del centro “ángeles encantadores - el tambo” del cantón Catamayo, provincia de Loja periodo 2020 - 2021. - Carrión Jara, Noelia Karina (2022)
In the present research, a synthesis of the information was carried out according to the study variables such as fine psychomotricity, activities of daily living, these are fundamental in the development of the autonomy of people with intellectual disabilities. This study aimed to determine the influence of fine psychomotricity in people with intellectual disabilities. The development of the research had a non-experimental field design, through the intervention, of a descriptive nature, of an explanatory type, with a quali-quantitative approach. Methods such as scientific, analytical-synthetic, descriptive were used, instruments were applied which are the Ozeretski adapted technical sheet that allowed to evaluate fine psychomotricity, an observation sheet adapted by Delia Martín where the difficulties in the two proposed variables were observed and finally the Survey was applied to parents to identify the activities of daily life of their children. The population was 30 people from the center "Ángeles Encantadores – El Tambo" and 30 parents, the sample was 10 people with intellectual disabilities who presented difficulties in fine psychomotricity and in the realization of activities of daily living and 10 parents who attend the center giving a total of 20 people, were referred by Mr. Pedro Chaunay, director of the center. The results obtained concluded that, in people with intellectual disabilities, fine psychomotricity is affected in terms of cutting with scissors, tearing, coloring, punching, fastening- unbuttoning and stringing, thus hindering the execution of the activities of daily living especially in hygiene and clothing activities, so an intervention proposal was determined that seeks to strengthen the processes and enhance the development of fine psychomotricity. Keywords: Psychomotor difficulties, Activities of daily living, Intellectual disability, Skills